THE INFLUENCE OF CULTURAL, SOCIAL, PERSONAL, AND PSYCHOLOGICAL ON CONSUMER PURCHASE DECISION- STUDY ON TONASA CEMENT PRODUCT IN MANADO CITY - Susanto, Aditya Budi (Sam Ratulangi University, 2016)
ABSTRACT There are some factors on the cultural, social, personal and psychological to customer purchase decision. This research is design to analyze the influence of cultural, social, personal, and psychological to customer purchase decision for Tonasa cement products in Manado city. Use the multiple regression analysis method, so the researcher can analyze the influence of the independent variable to dependent variable, which is employee performance. The independent variable in this research is cultural, social, personal, and psychological. Based on the result on the analysis of data using multiple linear regression analysis techniques, the t test, obtained results which indicate that the influence of cultural, social, personal, and psychological to customer purchase decision for Tonasa cement products in Manado city. This result is there is no significant difference for cultural, social, personal, psychological to costumers purchase decision for Tonasa cement product in Manado city. Keywords: Cultural, Social, Personal, Psychological, Customer Purchase Decision